Education Program 4.0 In The Making Indonesia 4.0 Roadmap And Its Implementation At Muhammadiyah Junior High School Of Ajibarang Indonesia - Wanda Nugroho Yanuarto; Joko Purwanto; Anton Jaelani (International Journal Of Community Service, 2022)
The As a result of the implementation of the Fourth Industrial Revolution, the world of education is being impacted by the application of technology across all aspects of learning in schools. One of the government's efforts to bring Indonesian life into line with the pace of technological advancement is the initiative Making Indonesia 4.0 (4.0 Indonesia). Education 4.0 in Indonesia is one of the initiatives aimed at transforming Indonesia into a 4.0 society. Education 4.0 in Indonesia is a program that was developed to improve the quality of education by incorporating technology into its activities, particularly in the classroom. We hope to learn about the 4.0 education program in Indonesia and the challenges it faces. We also hope to learn about how 4.0 education can be implemented in schools, specifically at Muhammadiyah Junior High School of Ajibarang, through this training. The participants in this training activity are all teachers from junior high schools in Banyumas Regency who are participating in this training activity. The participants in this training were 36 teachers from Muhammadiyah Junior High School of Ajibarang , who served as a model. Specifically, there are four stages to this training method: the presentation stage, peer teacher stage, class observation stage, and final performance evaluation stage. The culmination of this training is the completion of education 4.0 at Muhammadiyah Junior High School of Ajibarang, which consists of three main steps, namely the development of an e-learning platform, the holding of an innovation workshop, and the participation of school and industry. According to the organizers, this activity will serve as an alternative to solving problems related to the implementation of education 4.0 at Muhammadiyah Junior High School of Ajibarang in an effort to develop a roadmap for Indonesia's transition to the Fourth Industrial Revolution.